2019
DOI: 10.3390/catal9070612
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Sulfamethoxazole Using Iron-Doped Titania and Simulated Solar Radiation

Abstract: This work examined the photocatalytic destruction of sulfamethoxazole (SMX), a widely used antibiotic, under simulated solar radiation using iron-doped titanium dioxide as the photocatalyst. Amongst the various iron/titania ratios examined (in the range 0%–2%), the catalyst at 0.04% Fe/TiO2 molar ratio exhibited the highest photocatalytic efficiency. The reaction rate followed pseudo-first-order kinetics, where the apparent kinetic constant was reduced as the initial concentration of SMX or humic acid increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 50 publications
1
18
0
Order By: Relevance
“…A strong influence of the water matrix on the photooxidation of methylparaben was previously reported by Velegraki et al [56]. Similarly, Tsiampalis et al [2], who studied the degradation of sulfamethoxazole with iron-doped titania, found a decrease in the degradation rate of this molecule Figure 7. Effect of the water matrix on the photocatalytic degradation of clofibric acid (30 mg/L of clofibric acid, 1 g/L of catalyst, 9.52 mW/cm 2 , room temperature).…”
Section: Influence Of Water Matrixsupporting
confidence: 57%
See 2 more Smart Citations
“…A strong influence of the water matrix on the photooxidation of methylparaben was previously reported by Velegraki et al [56]. Similarly, Tsiampalis et al [2], who studied the degradation of sulfamethoxazole with iron-doped titania, found a decrease in the degradation rate of this molecule Figure 7. Effect of the water matrix on the photocatalytic degradation of clofibric acid (30 mg/L of clofibric acid, 1 g/L of catalyst, 9.52 mW/cm 2 , room temperature).…”
Section: Influence Of Water Matrixsupporting
confidence: 57%
“…A strong influence of the water matrix on the photooxidation of methylparaben was previously reported by Velegraki et al [56]. Similarly, Tsiampalis et al [2], who studied the degradation of sulfamethoxazole with iron-doped titania, found a decrease in the degradation rate of this molecule when the reaction is conducted in secondary treated wastewater and diluted wastewater.…”
Section: Influence Of Water Matrixmentioning
confidence: 55%
See 1 more Smart Citation
“…A source of clean water is important for various industrial, social and economic development sectors; therefore, it has to be constantly monitored for impurities. Increased human activity has introduced a wide range of toxic chemicals including inorganic (e.g., chromium, mercury, lead) and organic (e.g., pesticides, surfactants, pharmaceuticals) pollutants into the aqueous environment [1,2]. A significant source of such polluting compounds is wastewater from the textile industry, which is classified as the most polluting of all industrial sectors in terms of effluent volume and its chemical content [3].…”
Section: Introductionmentioning
confidence: 99%
“…At 30% loading of calcite in titania exhibited the best degradation of tetracycline under neutral conditions. Iron doped titania was studied by Tsiampalis for sulfamethaxoazole degradation under solar radiation [ 141 ]. Moosavi et al reported the degradation of Amoxicillin using supported titania nano photocatalysts [ 142 ].…”
Section: Applications Of Titania As Photocatalystmentioning
confidence: 99%